SIKAP TERHADAP FASHION YANG SUSTAINABLE MEMPENGARUHI NIAT MEMBELI - Nurfiani; Susanti; Malahayati (JURNAL KREASI RAKYAT, 2024)
This research aims to determine the factors influencing the intention to purchase ethical fashion with the variables sustainability, awareness, and trust. This research was conducted in Banda Aceh while distributing the questionnaire online by Google Form. This research uses a quantitative approach, using SPSS 25 statistical equipment with a sample of 107 respondents. The data analysis technique in this research uses multiple linear regression analysis. The research results show that sustainable, awareness, and trust variables influence purchasing intention.